基于SolidWorks的输送链三维造型及运动仿真的实现 - 李英杰; 洪林 (Jixie chuandong)
For a special kind of slow-speed overloading conveyor chain-U-type slide constrained conveyor chain,the 3DModeling of U-shaped conveyor chain is built by use of SolidWorks software,the assembling of it is carried out in terms of path matching and the detailed and specific operating steps is described.The implement method of physical motion simulation of U-type slide constrained conveyor chain transmission is given.It provides some guiding significance for digital design and manufacturing of chain transmission in engineering applications.